Comparison of pH and Viscosity of Unstimulated Saliva in Type 2 Diabetic Patients and Control Group - Mohiti, Azra; Ghadiri-Anari, Akram; Entezary, Fatemeh (Journal of Dental School, 2019)
Objectives: Diabetes mellitus is one of the most common chronic diseases that may cause irreversible complications. This disease can affect the salivary glands and oral health. Among physical and chemical alterations, changes in the pH and viscosity of saliva are particularly important. The aim of this study was to compare the pH and viscosity of unstimulated saliva in diabetic patients and non-diabetic controls. Methods: In the present case-control study, three groups consisted of 36 controlled type 2 diabetic patients, 36 uncontrolled type 2 diabetic patients and 36 healthy controls were recruited and matched by age and sex. Their unstimulated cumulative saliva was collected for five minutes by the spitting method and the pH of samples was measured by a digital pH meter. The viscosity of saliva samples was assessed by comparing the sample displacement rate with that of control fluids at mm/10 seconds. Data were analyzed by SPSS version 20 via ANOVA and Bonferroni multiple comparisons test. P value less than 0.05 was considered statistically significant. Results: A significant inverse correlation was found between the saliva pH and hyperglycemia (P<0.0001). A significant relationship was noted between viscosity and severity of diabetes mellitus (P<0.0001). The pH of saliva in uncontrolled diabetic patients was significantly lower than that of controlled type 2 diabetic patients and non-diabetic control group (P<0.05). The viscosity of saliva in diabetic patients with well and poorly controlled hyperglycemia was more than that of the control group (P<0.009 and P<0.0001, respectively). Conclusion: Diabetes mellitus causes a reduction in saliva pH and increases the viscosity of saliva, which can cause qualitative and quantitative changes in the saliva and oral health.